The progress to establish optimal animal models for the study of acute-on-chronic liver failure - Zhai, Hengben; Zhang, Jinming; Shang, Dabao; Zhu, Chuanwu; Xiang, Xiaogang (Frontiers in Medicine, 2023)
Acute-on-chronic liver failure (ACLF) defines a complicated and multifaceted syndrome characterized by acute liver dysfunction following an acute insult on the basis of chronic liver diseases. It is usually concurrent with bacterial infection and multi-organ failure resulting in high short-term mortality. Based on the cohort studies in ACLF worldwide, the clinical course of ACLF was demonstrated to comprise three major stages including chronic liver injury, acute hepatic/extrahepatic insult, and systemic inflammatory response caused by over-reactive immune system especially bacterial infection. However, due to the lack of optimal experimental animal models for ACLF, the progress of basic study on ACLF is limping. Though several experimental ACLF models were established, none of them can recapitulate and simulate the whole pathological process of ACLF patients. Recently, we have developed a novel mouse model for ACLF combining chronic liver injury [injection of carbon tetrachloride (CCl4) for 8 weeks], acute hepatic insult (injection of a double dose CCl4), and bacterial infection (intraperitoneal injection of Klebsiella pneumoniae), which could recapitulate the major clinical features of patients with ACLF worsened by bacterial infection.